Prevalence and factors associated with obesity and overweight among nurses in Mulago National Referral Hospital: A cross-sectional study. - mbabazi ceaser; Ann Noland Oketayot (Student's Journal of Health Research Africa, 2026)
Background: Obesity and overweight are major risk factors for cardiovascular disease and are increasingly affecting healthcare workers. This study determined the prevalence of obesity and overweight and associated factors among nurses at Mulago National Referral Hospital, Uganda. Methods: It was a cross-sectional design. Nurses of different cadres working at Mulago hospital who were present were studied. All nurses were contacted, and those who consented were recruited. Data was collected using a modified WHO-STEPS tool. All nurses were sampled, and those who consented were included in the study. Data was entered into EpiData v4.6 and analysed using STATA 14. Categorical data were summarized as frequencies and percentages. The prevalence of obesity and overweight was estimated as a proportion of the entire sample size. An analysis of factors associated was done by modified Poisson regression reporting robust standard errors. Ethical approval was sought from MakSOMREC. Results: A total of 173 nurses participated, of whom 71.1% were female. The prevalence of overweight was 36.9%, while obesity was 33.5%. Overall, 70.5% of nurses were either overweight or obese. Abdominal obesity was 61.8% using waist circumference and 36.9% using waist-to-hip ratio. Female sex (adjusted PR=0.84, 95%CI 0.76–0.93) and having one job (adjusted PR=0.84, 95%CI 0.72–0.97) were independently associated with obesity and overweight. Conclusions: Obesity and overweight are high among nurses in Mulago hospital, with the female gender more at risk. Recommendations: Workplace wellness programmes promoting healthy nutrition, physical activity, and regular obesity screening should be implemented among nurses.